Who Suffers From Pharmaceutical Poverty and What Are Their Needs? Evidence From a Spanish Region - Rubio-Valera, Maria; Marqués-Ercilla, Silvia; Peñarrubia-María, M Teresa; Urbanos-Garrido, Rosa M.; Borrell, Carme; Bosch, Jordi; Sánchez-Viñas, Alba; Aznar-Lou, Ignacio (Frontiers in Pharmacology, 2021)
Background: Pharmaceutical poverty occurs when a patient cannot afford the cost of prescribed medication and/or medical products. Non-profit organisations are covering the cost of medication to those patients in some contexts. The aim of the study was to describe the population of beneficiaries of the PB, a non-governmental organization based on Primary Healthcare system, which provides free of charge access to medicines, and their utilization pattern of medicines and healthcare products. Methods: This was an observational study using PB beneficiary data collected between November 2017 and December 2018 in Catalonia. The Catalan Health Service provided information from the general population. A descriptive analysis of the beneficiaries’ characteristics was conducted and compared to general population. Results: The beneficiaries (N=1206) were mainly adults with a low level of education, unemployed, with functional disability and with ≥1 children. Compared with the general population, the beneficiaries were older, had a lower level of education, showed a higher prevalence of functional disability, were less likely to be Spanish, and more likely to be divorced and unemployed. The beneficiaries were polymedicated and most were using medication related to the nervous (79%), musculo-skeletal (68%) and cardiovascular system (56%) and alimentary tract and metabolism (68%). Almost 19% of beneficiaries used healthcare products. Female beneficiaries were older and more likely to be divorced or widowed, employed and with children. Compared to men, women were more likely to use medicines for pain and mental disorders. The paediatric group used medications for severe, chronic conditions (heart diseases, autoimmune diseases, conduct disorders and attention deficit hyperactivity disorder). Conclusions: Patients with severe, chronic and disabling conditions are affected by pharmaceutical poverty. While the system of co-payment remains unchanged, family physicians and paediatricians should explore economic barriers to treatment and direct their patients to resources that help to cover the cost of treatment.